The right to a name: Back to the future - Alim K. Ulbashev (Цифровое право, 2020)
This article focuses on the right to a name, which in private law doctrine is traditionally considered a basic human right. The meaning of this right is indisputable and holds a fundamental value for everyone, since a name individualizes each person. However, the purpose of this article is not to tell the history of this right, but to study its nature. The development of the internet and digital technologies has made it possible to take a fresh look at the right to a name; when registering on social media, a person also uses his or her name, and in some cases acquires a pseudonym (nickname). In this study, the author aims at answering the question of what, in the era of the internet, is truly meant by the right to a name. Methodologically, there are two general approaches to understand the right to a name: the first one is AngloAmerican and the second one is European. While it is typical for common-law countries to consider a name as an element of privacy, in continental legal tradition the right to a name is considered as a type of personal right, as well as one of the conditions of legal capacity. Both approaches are re-examined in this study. Having started with the right to a name, in the final paragraph of the article the author reaches the issue of the right to a pseudonym. This topic is illustrated with the case of “the fight against rootless cosmopolitism”, when many representatives of the Jewish intelligentsia in the Soviet Union became victims of discrimination, at a time when it public authorities assumed that the use of a pseudonym was dangerous as they could lose control over the people; ironically, many modern states have declared the same criticism of the right to a nickname regarding the internet. This example clearly shows that, throughout history, non-democratic regimes have systematically attacked and diminished the right to a name. It is concluded that the advent of new technologies has not changed the essence of a name. Therefore, any unreasonable limitation of the right to a name and the right to a pseudonym should be defined as a violation of the basic principles of democracy and the rule of law.